COVID-19 Vaccination Response in Patients with Multiple Sclerosis Treated with Ofatumumab in the United States: A Medical Record Review - Rahul H. Dave; Heidi Crayton; Augusto Miravalle; Ming-Hui Tai; Kerri Wyse; Katherine Houghton; Abby Hitchens; Regina Berkovich (Neurology and Therapy)
Abstract Introduction Real-world data are required to provide a greater understanding of the impact of ofatumumab on the ability to mount an effective immune response following the receipt of approved COVID-19 vaccinations. This retrospective real-world analysis aimed to describe the humoral immune response to COVID-19 vaccination during ofatumumab treatment in patients with multiple sclerosis (MS). Methods Data from patients with MS treated with ofatumumab who were fully vaccinated against COVID-19 infection were abstracted from medical charts at four clinical sites in the USA. Patient characteristics and humoral response were summarized descriptively. Differences in humoral response were documented on the basis of vaccination status during ofatumumab treatment (i.e., after full vaccination and after booster vaccination) and prior disease-modifying treatment (DMT) exposure (i.e., DMT naïve, prior anti-CD20/sphingosine 1-phosphate [S1P] therapy, prior non-anti-CD20/S1P therapy). The sample size precluded formal statistical analysis. Results Thirty-eight patients were included. The mean (standard deviation) duration of ofatumumab treatment upon data collection was 20.4 (4.6) months (treatment ongoing for 35 [92%] patients). Definitive humoral response after full vaccination was documented for 34 patients, of whom 20 (60%) were seropositive. Definitive humoral response after booster vaccination was documented among five patients, of whom three (60%) were seropositive. Among patients who were DMT naïve prior to ofatumumab (n = 15), 73% were seropositive; among patients exposed to prior anti-CD20/S1P therapy (n = 14), 33% were seropositive; and among patients exposed to prior non-anti-CD20/S1P therapy (n = 9), 56% were seropositive. Patients naïve to DMT had been living with an MS diagnosis for a shorter duration than those experienced with DMTs. Conclusion Patients with MS receiving ongoing treatment with ofatumumab can mount a positive humoral response to a COVID-19 vaccination. Prior treatment with anti-CD20 or S1P DMTs may be a risk factor for lower humoral response.